Shorebird feeding specialists differ in how environmental conditions alter their foraging time. (28th November 2019) - van der Kolk, Henk-Jan; Ens, Bruno J; Oosterbeek, Kees; Bouten, Willem; Allen, Andrew M; Frauendorf, Magali; Lameris, Thomas K; Oosterbeek, Thijs; Deuzeman, Symen; de Vries, Kelly; Jongejans, Eelke; van de Pol, Martijn
Abstract: Feeding specialization is a common cause of individual variation. Fitness payoffs of specialization vary with environmental conditions, but the underlying behavioral mechanisms are poorly understood. Such mechanistic knowledge, however, is crucial to reliably predict responses of heterogeneous populations to environmental change. We quantified spatiotemporal allocation of foraging behavior in wintering Eurasian oystercatchers ( Haematopus ostralegus ), a species in which feeding specialization can be inferred from bill shape. We combined global positioning system (GPS) and accelerometer data to quantify foraging time of 64 individuals for every tidal period in one or two winter seasons. Individuals varied widely in foraging time (3.7–6.5 h per tidal period) and individuals that spend more time foraging had lower inferred survival. Feeding specialization appeared a major determinant of individual variation in foraging time and its spatiotemporal allocation. Visually hunting worm specialists foraged more during day time and complemented intertidal foraging with grassland foraging when the exposure of intertidal flats was limited and nights were well illuminated. Shellfish specialists increased total foraging time in cold weather, whereas foraging time of worm specialists decreased as frosty grasslands became inaccessible. Our results imply that worm specialists may be most sensitive to cold snaps and daytime disturbance, whereas shellfish specialists are most sensitive to high water levels. These behavioral responses can be implemented in population models to predict the vulnerability of heterogeneous populations to environmental change and, thereby, provide a shortcut to long-term population studies that require fitness data across many years and conditions to make similar projections. Abstract : Populations consist of different types of individuals. Predicting how heterogeneous populations of long-lived species respond to environmental change is hard as it takes decades to quantify how fitness varies among individuals in different environmental conditions. We studied the behavior of GPS-tracked oystercatchers and showed how foraging time is differentially affected by environmental conditions among individuals that specialize in different prey. This knowledge can be implemented in models to predict the vulnerability of heterogeneous populations to environmental change.